2021
DOI: 10.1038/s41598-021-94184-7
|View full text |Cite
|
Sign up to set email alerts
|

Low pan-immune-inflammation-value predicts better chemotherapy response and survival in breast cancer patients treated with neoadjuvant chemotherapy

Abstract: Blood-based biomarkers reflect systemic inflammation status and have prognostic and predictive value in solid malignancies. As a recently defined biomarker, Pan-Immune-Inflammation-Value (PIV) integrates different peripheral blood cell subpopulations. This retrospective study of collected data aimed to assess whether PIV may predict the pathological complete response (pCR) to neoadjuvant chemotherapy (NAC) in Turkish women with breast cancer. The study consisted of 743 patients with breast cancer who were sche… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
65
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 41 publications
6
65
1
Order By: Relevance
“…For example, a high NLR is usually considered as an indicator of a poor prognosis, 19,38 but NLR failed to show independent value in the multivariate Cox analysis in other studies when identifying patients with a pathological complete response or achievement of disease-free status. 39,40 A similar dilemma has also been found in other biomarkers, such as MLR. These discrepancies could be attributed to patient heterogeneity, differences in the definitions of cutoff points, and so on.…”
Section: Discussionsupporting
confidence: 56%
“…For example, a high NLR is usually considered as an indicator of a poor prognosis, 19,38 but NLR failed to show independent value in the multivariate Cox analysis in other studies when identifying patients with a pathological complete response or achievement of disease-free status. 39,40 A similar dilemma has also been found in other biomarkers, such as MLR. These discrepancies could be attributed to patient heterogeneity, differences in the definitions of cutoff points, and so on.…”
Section: Discussionsupporting
confidence: 56%
“…Fifteen studies encompassing 4942 patients were included in the meta-analyses [ 32 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The available studies were conducted on several tumors, including CRC, melanoma, breast cancer, and non-small cell lung cancer ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study evaluated both patients treated with immunotherapy (nivolumab and pembrolizumab alone) and targeted therapy with BRAF inhibitors/MEK inhibitors, and separate data for these treatment types were included in the subgroup analyses [ 32 ]. Ten studies included Caucasian patients [ 32 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 48 ], while five studies were conducted in the Far East [ 44 , 45 , 46 , 47 , 49 ]. Most studies had a low risk of bias according to the NOS ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As PIV is a relatively novel biomarker, few studies on PIV have been reported thus far. A previous study ( 50 ) showed that a low PIV value predicts better chemotherapy response and survival in breast cancer patients treated with neoadjuvant chemotherapy. Another previous study ( 20 ) showed that PIV is a new and potent predictor of OS in HER-2-positive advanced BC patients treated with first-line trastuzumab–pertuzumab-containing biochemotherapy.…”
Section: Discussionmentioning
confidence: 99%